2020
DOI: 10.1002/maco.202011952
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endemic Chilean plant‐based Chañar extract (Geoffroea decorticans) as an inhibitor of corrosion for A36 steel under a saline environment

Abstract: The use of inhibitors is one of the most practical modern methods in preventing and protecting against metal and alloy pipe corrosion. Exploring such additional inhibitors, particularly of natural origins, has become a key area of research. The present work, thus, evaluates the extract of a desert plant fruit, endemic to northern Chile, called Chañar (Geoffroea decorticans), as an inhibitor for the corrosion of A36 steel under a saline environment. Extract inhibition efficiency was evaluated by mass loss, pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…On the other hand, if the E corr shift <±85 mV, the inhibitor is of mixed electrochemical type. [ 31,32 ] In our study, the maximum displacement of E corr was −24.5 mV. These findings suggest that our inhibitor has mixed electrochemical behavior, as it acts by decreasing the anodic dissolution rate of the steel and reducing H + proton.…”
Section: Resultsmentioning
confidence: 49%
“…On the other hand, if the E corr shift <±85 mV, the inhibitor is of mixed electrochemical type. [ 31,32 ] In our study, the maximum displacement of E corr was −24.5 mV. These findings suggest that our inhibitor has mixed electrochemical behavior, as it acts by decreasing the anodic dissolution rate of the steel and reducing H + proton.…”
Section: Resultsmentioning
confidence: 49%
“…Also, a large number of papers are dedicated to finding ecologically friendly corrosion inhibitors obtained from extracts of various plants. [9][10][11][12][13][14][15] In the 1990s, Hinton [16] showed that rare earth metal chlorides (Y, Nd, Ce, La, etc.) are effective corrosion inhibitors of many metals and alloys in NaCl solutions, including steels.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a large number of papers are dedicated to finding ecologically friendly corrosion inhibitors obtained from extracts of various plants. [ 9–15 ]…”
Section: Introductionmentioning
confidence: 99%